Bandura's Social Cognitive Theory and Its Implementation in Markeso Mudo's Garingan Ludrukan Monologue - Welly Suryandoko (Universitas Negeri Medan, 2023)
This paper aims to create works of art with Bandura's social cognitive theory approach consisting of a) Attention (attention), b) Retention, c) Motion Reproduction and d) Motivation as a foundation in the creative process of art learning in monologue courses in the Drama Concentration, Drama, Dance and Music Education Study Program (Sendratasik) Faculty of Language and Arts, Surabaya State University. This lecture is a type of practice with a total of 4 credits, students are directed to practice directly through various methods, strategies and competency content contained in the course. The focus in the current discussion is to practice the Monologue Ludrukan Garingan Markeso Mudo is a competency achievement that will be obtained by students if the stages can be carried out according to the procedure. The implementation of the Ludrukan Garingan Markeso Mudo Monologue is simulated in public spaces targeting crowded places such as markets, stalls or other public spaces that are in accordance with the needs of the actor's concept. The application of Bandura's Social Cognitive Theory as a tool to produce student process space in obtaining structured steps before implementing in the Monologue Ludrukan Garingan Markeso Mudo. Finally, it can obtain a good implementation formulation in practice in the field